Loneliness and Social Isolation in Older Adults - Ohiokpehai, Jafar; Gammack, Julie K.; Siddiqui, Mehwish; Nyahoda, Tarisai (Missouri Medicine, 2025)
Loneliness is a distressing feeling that accompanies the perception that one's social needs are not being met by the quantity or the quality of one's social relationships. It is a subjective experience of a perceived discrepancy between the preferred and actual level and quality of social interaction.1 In contrast, social isolation is an objective lack of meaningful and sustained social contacts, interactions, networks or belonging. Social isolation describes a paucity of social relationships, while loneliness depicts the lived experience and recognition of that absence.2 Although sometimes used interchangeably, loneliness and social isolation are unique conditions that share overlapping features, risk factors, and consequences. One may feel lonely with or without being socially isolated, just as one may or may not feel lonely despite being alone. These conditions do often coexist, as demonstrated in a study of older adults during the COVID-19 pandemic. In this study, both loneliness and social isolation were present in one-third of individuals; one-third of those who were lonely were also socially isolated, and 94% of those who were socially isolated were also lonely (Figure 1).3 Loneliness is neither a disease nor classified as a mental health disorder. Some have suggested that loneliness is a new geriatric syndrome: a health condition highly prevalent in older adults that is multifactorial in cause and contributes to adverse health outcomes. The COVID-19 pandemic unmasked and magnified the detrimental effects of social isolation and loneliness in older populations. We are learning more about the physical and psychological impacts of loneliness and ways to mitigate social isolation.
Keywords: Aged; Aged, 80 and over; COVID-19; Female; Humans; Loneliness; Male; SARS-CoV-2; Social Isolation